E.B. O'Callaghan, Laws and Ordinances of New Netherland, 1638-1674, at 47 (1868); N.Y. Col. MSS, IV. 216 - (:unkn) unknown (My University, 1645)
Prohibited the selling and bartering of firearms and ammunition with "the Indians."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES